Perbedaan Perbedaan Tingkat Pengetahuan Kaidah Dasar Bioetika Pada Mahasiswa Program Studi Kedokteran Fakultas Kedokteran Universitas Mulawarman: Differences in the Level of Knowledge of Basic Principles of Bioethics among Students of the Medical Study Program, Faculty of Medicine, Mulawarman University - Rahmania (Jurnal Medika : Karya Ilmiah Kesehatan, 2024)
Bioethics is a new discipline that is a combination of biological knowledge (biology) with knowledge of the human value system. This study aims to determine the difference in the level of knowledge of the basic rules of bioethics in students who have never had and have had a bioethics lecture at B7M1 Medical Study Program, Faculty of Medicine, Mulawarman University. This research is a quantitative study with observational analytic research design using cross sectional design. The sampling technique used total sampling. The source of research data was obtained from primary data through filling out the basic bioethics test questionnaire. Bivariate analysis using the Mann-Whitney test. The results showed that the p-value> 0.05 (p=0.173), so it was concluded that there was no significant difference in the level of knowledge of the basic rules of bioethics in students who had never had and had received bioethics lectures at B7M1 Medical Study Program, Faculty of Medicine, Mulawarman University. Keywords: Basic rules of bioethics, level of knowledge, medical study program students